Using TOCFL Reading Application to Improve Reading Mandarin Ability - Vincentius Valiandy Jiuangga; Mei Rianto Chandra; Agatha Angelina Jiuangga; Isadora Isadora (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
This study aims to improve student's reading skills and prepare them for the Novice A1 Reading TOCFL (Test of Chinese as a Foreign Language) exam. The tool in this study was the TOCFL Reading application which contained 25 practice questions, with the types of questions: answering based on the pictures given & answering based on the questions given. Respondents to this study were 19 students of English literature at Ma Chung University who had only been learning Mandarin for about one year. This research method is the action research method. Students are asked to do exercises in the TOCFL Reading application two times. The results of this study were that after two tests were carried out in class, all students experienced an increase in scores from 4 points to 40 points; this proves that learning with the TOCFL application can help students improve their reading skills and help them prepare for the TOCFL exam.